Bituminous mix response to plastic deformations: comparison of the spanish nlt-173 and une-en 12697-22 wheel-tracking tests (2012)
Rutting severely damages flexible pavements. It causes the loss of road surface regularity, which evidently has a negative impact on the quality of service to users. Of the various kinds of laboratory test used to assess plastic deformations in pavement layers, simulation tests are an extremely important type. The objective of this research study was to evaluate and determine the differences between the wheel-tracking test when performed in the laboratory, according to the Spanish NLT-173 regulations and the wheel-tracking test when performed according to UNE-EN 12697-22 regulations. When the CE marking for bituminous mixes was established in 2008, this test became mandatory. The aim of this research study was to analyze the equivalence of the specification limit values in both sets of regulations.